Proporsionalitas dan Akuntabilitas dalam Tata Kelola Digital Atas Pembatasan Akses Internet Bagi Anak di Indonesia - Eka Nurhikmah; Nelvina Djaja; Laurenzia Luna (JURNAL USM LAW REVIEW, 2025)
This study examines the policy on restricting children’s internet access following the enactment of Government Regulation No. 17 of 2025 through the lens of Administrative Law and international children’s rights. The growing use of digital platforms by children offers educational benefits but simultaneously exposes them to harmful content, digital exploitation, privacy risks, and potential technology addiction. The study addresses the need for a regulatory framework that ensures child protection while upholding proportionality, justice, and Indonesia’s obligations under the CRC and ICCPR. Using a normative juridical method with statutory and comparative approaches, this research analyses national regulations and compares them with international practices, particularly in Singapore. The novelty of this study lies in its focus on children as a vulnerable group often overlooked in internet restriction debates and its integrative analysis linking national administrative law with international child rights standards. The findings indicate that Government Regulation No. 17 of 2025 constitutes a progressive step toward strengthening child protection in the digital sphere. However, several challenges remain, including unclear age-verification standards, risks of data leakage, and potential limitations on children’s rights to access information and participate in digital environments. This study concludes that clear technical guidelines, robust accountability mechanisms for Electronic System Providers, and enhanced parental digital literacy are essential to ensure effective, proportional, and equitable implementation of the policy.   Penelitian ini menganalisis kebijakan pembatasan akses internet bagi anak setelah diterbitkannya PP No. 17 Tahun 2025 dari perspektif Hukum Administrasi Negara (HAN) dan hak anak internasional. Peningkatan penggunaan platform digital oleh anak memberikan manfaat pendidikan, tetapi juga menimbulkan risiko konten berbahaya, eksploitasi digital, pelanggaran privasi, serta potensi kecanduan teknologi. Penelitian ini menekankan pentingnya regulasi yang tidak hanya berorientasi pada perlindungan anak, tetapi juga selaras dengan prinsip keadilan, proporsionalitas, serta kewajiban Indonesia berdasarkan CRC dan ICCPR. Metode yang digunakan adalah yuridis normatif dengan pendekatan peraturan dan perbandingan, termasuk meninjau praktik negara lain seperti Singapura. Kebaruan penelitian terletak pada fokus terhadap anak sebagai kelompok rentan yang kerap terabaikan dalam diskursus pembatasan internet serta analisis integratif yang menghubungkan HAN dengan standar hak anak internasional. Hasil penelitian menunjukkan bahwa PP No. 17 Tahun 2025 merupakan langkah progresif dalam penguatan perlindungan anak di ruang digital, namun implementasinya masih menghadapi tantangan terkait standar verifikasi usia, risiko kebocoran data, serta potensi pembatasan hak anak atas informasi dan partisipasi. Penelitian ini menyimpulkan perlunya pedoman teknis yang jelas, mekanisme akuntabilitas yang kuat bagi PSE, serta peningkatan literasi digital orang tua untuk memastikan implementasi kebijakan yang efektif, proporsional, dan berkeadilan.